Tau and tauopathies across primate species: implications for modeling neurodegenerative disorders - Julia C. Colwell; Julia C. Colwell; Marina E. Emborg; Marina E. Emborg; Marina E. Emborg (Frontiers in Aging Neuroscience)
Tauopathies are neurodegenerative disorders characterized by the abnormal accumulation and aggregation of hyperphosphorylated tau protein. They can be primary or secondary depending on whether tau inclusions are the predominant pathology (e.g.: frontotemporal dementia related to tau) or are found with other proteinopathies (e.g.: Alzheimer’s disease), respectively. Currently, there are no effective treatments to prevent or slow down progressive tau accumulation. Animal models play a critical role in the efforts to unravel the mechanisms leading to tauopathies and identifying therapeutic targets. Nonhuman primates (NHPs) present several advantages for the study of tauopathies, as they have complex neuroanatomy and behavior that resembles human traits, and their tau gene and protein are highly conserved. Moreover, aged NHPs, like humans, can present various tau inclusions in their brains, although whether NHPs can develop human-like tau-related neurodegenerative disorders is currently debated. The main goal of this review is to analyze available reports on tau pathologies and models of tauopathies in NHPs considering the complexity of the tau protein and associated tau pathologies. Here, we first summarize current available information on human and NHP tau under physiological conditions in order to highlight species differences and gaps in knowledge. We then analyze reports on tau pathologies in aged NHPs compared to human aging and tauopathy, followed by an evaluation of current and emerging NHP models of tauopathy. Lastly, we discuss the practical and ethical challenges of doing tauopathy research in NHPs, and how to best leverage it to ultimately find solutions for patients with these disorders.